2010
DOI: 10.1016/j.str.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structural Analysis of Importin-β Flexibility: Paradigm for Solenoid Protein Structures

Abstract: The structure of solenoid proteins facilitates a higher degree of flexibility than most folded proteins. In importin-β, a nuclear import factor built from 19 tandem HEAT repeats, flexibility plays a crucial role in allowing interactions with a range of different partners. We present a comprehensive analysis of importin-β flexibility based on a number of different approaches. We determined the crystal structure of unliganded Saccharomyces cerevisiae importin-β (Kap95) to allow a quantitative comparison with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 62 publications
12
84
0
Order By: Relevance
“…The overall conformation of the solenoid (i.e. its diameter, curvature and pitch) varies from protein to protein, and is also affected by the interactions formed with their binding partners (Conti et al, 2006;Lee et al, 2000;Forwood et al, 2010). For example, structural comparison of the karyopherin importin β with and without the cargo has revealed substantial differences in the curvature of the solenoid (Cingolani et al, 1999(Cingolani et al, , 2000.…”
Section: Structural Properties Of Heat Repeatsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall conformation of the solenoid (i.e. its diameter, curvature and pitch) varies from protein to protein, and is also affected by the interactions formed with their binding partners (Conti et al, 2006;Lee et al, 2000;Forwood et al, 2010). For example, structural comparison of the karyopherin importin β with and without the cargo has revealed substantial differences in the curvature of the solenoid (Cingolani et al, 1999(Cingolani et al, , 2000.…”
Section: Structural Properties Of Heat Repeatsmentioning
confidence: 99%
“…2). The structural flexibility of HEAT repeats has been directly characterized by spectroscopic approaches (Tsytlonok et al, 2013) as well as by small angle X-ray scattering (Forwood et al, 2010). Molecular dynamics simulations have also demonstrated that, when external forces are applied at the ends of the molecule, the HEAT repeats exhibit unique elastic properties similar to a Hookean spring, whereby the extension is proportional to the tension applied (Grinthal et al, 2010;Kappel et al, 2010).…”
Section: Structural Properties Of Heat Repeatsmentioning
confidence: 99%
“…2(a) Q eliminate surface exposed hydrophobic residues on the accessible interface, and mutation D 23 P introduces a helixbreaking residue at the C-terminus of helix H2.…”
Section: And Inmentioning
confidence: 99%
“…The ARM core generates a cargo-binding surface ideal to function as a static NLS-binding groove (46). This is very different from the HEAT-repeated architecture of ␤-karyopherins that form superhelical solenoids of remarkable structural flexibility (7,8,44). The results presented in this paper, together with previous structural (18) and biochemical (20) reports on importin ␣5 (Fig.…”
Section: Discussionmentioning
confidence: 56%